Effects of Maternal Responsiveness on Infant Responsiveness and Behavior in the Still‐Face Task. (29th July 2014) - Bigelow, Ann E.; Power, Michelle
<x xml:space="preserve">Abstract</x> The effects of maternal responsiveness on infant responsiveness and behavior in the Still‐Face Task were longitudinally examined through infants' first 3 months. Maternal vocal responsiveness and infant vocal and smiling responsiveness significantly increased when infants were 2 months of age. Mothers showed continuity of individual differences in vocal responsiveness from the infants' newborn period. Maternal responsiveness predicted infant responsiveness within and across sessions. Compared with infants with low‐responsive mothers, infants with high‐responsive mothers were more attentive and affectively engaged during the Still‐Face Task from 1 month of age. Infants with high‐responsive mothers discriminated between the task phases with their smiling at 1 month, a month before infants with low‐responsive mothers did so. Infants in both groups discriminated between the phases with their attention and nondistress vocalizations throughout their first 3 months. Results suggest that maternal responsiveness influences infant responsiveness and facilitates infants' engagement and expectations for social interaction.